Role of stilbenes against insulin resistance: A review - Shazmeen (Wiley, 2021)
Abstract Insulin resistance (IR) is a state characterized by the inability of tissues to utilize blood glucose particularly liver, muscle, and adipose tissues resulting in hyperglycemia and hyperinsulinemia. A close relationship exists between IR and the development of type 2 diabetes (T2D). Therefore, therapeutic approaches to treat IR also improve T2D simultaneously. Scientific evidence has highlighted the major role of inflammatory cytokines, reactive oxygen species (ROS), environmental & genetic factors, and auto‐immune disorders in the pathophysiology of IR. Among therapeutic remedies, nutraceuticals like polyphenols are being used widely to ameliorate IR due to their safer nature compared to pharmaceutics. Stilbenes are considered important metabolically active polyphenols currently under the limelight of research to cope with IR. In this review, efforts are made to elucidate cellular and subcellular mechanisms influenced by stilbenes including modulating insulin signaling cascade, correcting glucose transport pathways, lowering postprandial glucose levels, and protecting β‐cell damage and its effects on the hyperactive immune system and proinflammatory cytokines to attenuate IR. Furthermore, future directions to further the research in stilbenes as a strong candidate against IR are included so that concrete recommendation for their use in humans is made.